Dibenzodiazepinone-type muscarinic receptor antagonists conjugated to basic peptides: Impact of the linker moiety and unnatural amino acids on M2R selectivity - Weinhart, Corinna G.; Wifling, David; Schmidt, Maximilian; Neu, Eduard; Höring, Carina; Clark, Timothy; Gmeiner, Peter; Keller, Max (European Journal of Medicinal Chemistry, 2021)
The family of human muscarinic acetylcholine receptors (MRs) is characterized by a high sequence homology among the five subtypes (M1R-M5R), being the reason for a lack of subtype selective MR ligands. In continuation of our work on dualsteric dibenzodiazepinone-type M2R antagonists, a series of M2R ligands containing a dibenzodiazepinone pharmacophore linked to small basic peptides was synthesized (64 compounds). The linker moiety was varied with respect to length, number of basic nitrogens (0–2) and flexibility. Besides proteinogenic basic amino acids (Lys, Arg), shorter homologues of Lys and Arg, containing three and two methylene groups, respectively, as well as D-configured amino acids were incorporated. The type of linker had a marked impact on M2R affinity and also effected M2R selectivity. In contrast, the structure of the basic peptide rather determined M2R selectivity than M2R affinity. For example, the most M2R selective compound (UR-CG188, 89) with picomolar M2R affinity (pKi 9.60), exhibited a higher M2R selectivity (ratio of Ki M1R/M2R/M3R/M4R/M5R: 110:1:5200:55:2300) compared to the vast majority of reported M2R preferring MR ligands. For selected ligands, M2R antagonism was confirmed in a M2R miniG protein recruitment assay.
CRIS-Team Scopus Importer:2021-04-02
Keywords: Basic amino acid; Dibenzodiazepinone derivative; Induced-fit docking; M2R antagonist; M2R selectivity; MR subtype selectivity; Muscarinic acetylcholine receptors; Peptide

Heteroaryl derivatives of suvorexant as OX1R selective PET ligand candidates: Cu-mediated 18F-fluorination of boroxines, in vitro and initial in vivo evaluation - Bolik, Kim-Viktoria; Hellmann, Jan; Maschauer, Simone; Neu, Eduard; Einsiedel, Jürgen; Riss, Patrick; Vogg, Nora; König, Jörg; Fromm, Martin; Hübner, Harald; Gmeiner, Peter; Prante, Olaf (EJNMMI Research, 2024)
Background: The orexin receptor (OXR) plays a role in drug addiction and is aberrantly expressed in colorectal tumors. Subtype-selective OXR PET ligands suitable for in vivo use have not yet been reported. This work reports the development of 18F-labeled OXR PET ligand candidates derived from the OXR antagonist suvorexant and the OX1R-selective antagonist JH112. Results: Computational analysis predicted that fluorine substitution (1e) and introduction of the fluorobenzothiazole scaffold (1f) would be suitable for maintaining high OX1R affinity. After multi-step synthesis of 1a–1f, in vitro OXR binding studies confirmed the molecular dynamics calculations and revealed single-digit nanomolar OX1R affinities for 1a–f, ranging from 0.69 to 2.5 nM. The benzothiazole 1f showed high OX1R affinity (Ki = 0.69 nM), along with 77-fold subtype selectivity over OX2R. Cu-mediated 18F-fluorination of boroxine precursors allowed for a shortened reaction time of 5 min to provide the non-selective OXR ligand [18F]1c and its selective OX1R congener [18F]1f in activity yields of 14% and 22%, respectively, within a total synthesis time of 52–76 min. [18F]1c and [18F]1f were stable in plasma and serum in vitro, with logD7.4 of 2.28 ([18F]1c) and 2.37 ([18F]1f), and high plasma protein binding of 66% and 77%, respectively. Dynamic PET imaging in rats showed similar brain uptake of [18F]1c (0.17%ID/g) and [18F]1f (0.15%ID/g). However, preinjection of suvorexant did not significantly block [18F]1c or [18F]1f uptake in the rat brain. Pretreatment with cyclosporine A to study the role of P-glycoprotein (P-gp) in limiting brain accumulation moderately increased brain uptake of [18F]1c and [18F]1f. Accordingly, in vitro experiments demonstrated that the P-gp inhibitor zosuquidar only moderately inhibited polarized, basal to apical transport of 1c (p < 0.05) and had no effect on the transport of 1f, indicating that P-gp does not play a relevant role in brain accumulation of [18F]1c and [18F]1f in vivo. Conclusions: The in vitro and in vivo results of [18F]1c and [18F]1f provide a solid basis for further development of suitable OXR PET ligands for brain imaging.
CRIS-Team Scopus Importer:2024-09-13
Keywords: Cu-mediated; F-18; Orexin receptor; PET; Suvorexant

N-Terminus to Arginine Side-Chain Cyclization of Linear Peptidic Neuropeptide y Y4Receptor Ligands Results in Picomolar Binding Constants - Konieczny, Adam; Conrad, Marcus; Ertl, Fabian J.; Gleixner, Jakob; Gattor, Albert O.; Grätz, Lukas; Schmidt, Maximilian F.; Neu, Eduard; Horn, Anselm; Wifling, David; Gmeiner, Peter; Clark, Timothy; et al. (Journal of Medicinal Chemistry, 2021)
The family of neuropeptide Y (NPY) receptors comprises four subtypes (Y1R, Y2R, Y4R, Y5R), which are addressed by at least three endogenous peptides, i.e., NPY, peptide YY, and pancreatic polypeptide (PP), the latter showing a preference for Y4R. A series of cyclic oligopeptidic Y4R ligands were prepared by applying a novel approach, i.e., N-terminus to arginine side-chain cyclization. Most peptides acted as Y4R partial agonists, showing up to 60-fold higher Y4R affinity compared to the linear precursor peptides. Two cyclic hexapeptides (18, 24) showed higher Y4R potency (Ca2+ aequorin assay) and, with pKi values >10, also higher Y4R affinity compared to human pancreatic polypeptide (hPP). Compounds such as 18 and 24, exhibiting considerably lower molecular weight and considerably more pronounced Y4R selectivity than PP and previously described dimeric peptidic ligands with high Y4R affinity, represent promising leads for the preparation of labeled tool compounds and might support the development of drug-like Y4R ligands.
CRIS-Team Scopus Importer:2021-12-03